Prevalence and prognostic impact of synchronous distant metastases in patients with oral tongue squamous cell carcinoma: a SEER-based study - Li, Yujiao; Ou, Xiaomin; Hu, Chaosu (Translational Cancer Research; Vol 7, No 3 (June 27, 2018): Translational Cancer Research, 2018)
Background: Oral tongue squamous cell carcinoma (OTSCC) is the most common malignancy of the oral cavity. The prognosis of OTSCC patients with distant metastasis is poor. We sought to explore prevalence and prognostic impact of synchronous distant metastases among patients with OTSCC in this study. Methods: Patients with histologically proven OTSCC were extracted from the Surveillance, Epidemiology and End Results (SEER) database between 2010 and 2014. We examined the relationship between tumor factors and distant metastases using Chi-squared tests and we evaluated the association between survival and different variables using the methods of Kaplan-Meier. Univariate analysis was performed using the log-rank test. Multivariate analyses with the Cox proportional hazards model were used to test the independent significance of the predictors, and two-tailed p-values less than 0.05 were considered statistically significant. Results: We finally identified 5,730 patients who were diagnosed with OTSCC and the most frequent site of distant metastases was lung, followed by bone. Some clinical characteristics, including age, gender, race, histological grade, T classification and N classification were independent risk factors for lung and bone metastasis. Higher T or N category, poorer differentiation and multiple distant metastases were associated with poorer overall survival (OS). For cancer-specific survival (CSS), age (P